The Trinitarian Life of God and the Communal Life of the Church in Augustine's Confessions - Anderson, Derek N. (My University, 1999)
In the Confessions, Augustine presents a vision of the church which relies heavily upon his understanding of the trinitarian nature of God. The church is the venue where God reveals himself to human beings as Trinity, as the Son and the Spirit work within the community in a saving way, redressing the problem of human sinfulness, nourishing the community's love, and preparing the church to participate in the trinitarian life of God in the eschaton. As he develops his understanding of the relationship between the Trinity and the church, Augustine describes the divine nature as being inherently relational, trinitarian, and he maintains that the activity of the Trinity within the church engenders loving relationships both among human beings and between the community as a whole and God. This analysis of Augustine's understanding of God's trinitarian activity in the church calls into question the validity of criticisms brought against Augustine's theology by commentators such as Jilrgen Moltmann, who contends that Augustine introduced deleterious tendencies into Western theology which gave rise to Modalistic conceptions of God and individualistic expressions of the doctrine of human nature. In fact in the Confessions, Augustine delineates a view of the church in which the health of the community is assured through the activity of the God whose life is expressed in terms of an eternal community of three persons.
Keywords: religious studies